Peer pressure and adolescents’ problem behavior - TINATINI BANDZELADZE; LUIZA ARUTIUNOV (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This research mainly aims to determine if and how much adolescent’s problem behaviors are influenced by their social circles. Researchers hypothesized that adolescent’s moral disengagement, or tolerance of deviant behavior, mediated the effect of their peers on their problem behavior.Method: The methodology used here is a correlational one. The information was gathered through the use of self-reported questionnaires. Around 150 young people (aged 14-18) participated in the study. Sixty youths with legal issues comprise the first group, while ninety youths without such problems comprise the second.Findings: According to the research results, adolescent’s problem behavior is best predicted by the problem behavior models they see in their peer groups. According to both correlational and regression analyses, adolescent problem behavior is negatively correlated with peer regulation of that behavior. A statistically significant mediator variable between peer control and delinquent behavior was moral disengagement. Increasing adolescent’s tolerance for deviant behavior weakens the correlation between peer pressure and negative behavior. Conclusions from this study support the use of a multi-system approach to preventing problem behavior in adolescents. When it comes to preventing deviant behavior in adolescents, the multi-system approach takes into account the adolescent’s traits and the impact of social factors like their peers and family.Implications/Novel Contribution: The proposed multi-factor theoretical model, which integrates the relevant individual and environmental characteristics linked to adolescent problem behavior, fully justifies the research’s theoretical value and novelty.